Fiscal Federalism in Theory and Practice. (International Monetary Fund, 1997)
Over the past few decades, a clear trend has emerged worldwide toward the devolution of spending and, to a lesser extent, revenue-raising responsibilities to state and local levels of government. One view is that the decentralization of spending responsibilities can entail substantial gains in terms of distributed equity and macroeconomic management. The papers in this volume, edited by Teresa Ter-Minassian, examine the validity of these views in light of theoretical considerations, as well as the experience of a number of countries.